2016
DOI: 10.5604/20831862.1208479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of far infrared rays emitting clothing on recovery after an intense plyometric exercise bout applied to elite soccer players: a randomized double-blind placebo-controlled trial

Abstract: The aim was to investigate the effects of far infrared (FIR) ray emitting clothes on indirect markers of exercise-induced muscle damage and physical performance recovery after a plyometric bout applied to soccer players. Twenty-one male players (18.9±0.6 years; 70.8±5.01 kg; 178.3±0.06 cm) performed 100 drop-jumps. Six hours after the bout, athletes put on FIR clothes (FIR) (density of 225 g·m-2, 88% far infrared rays emitting polyamide 66 Emana yarn (PA66) fibre, 12% Spandex, emissivity of 0.88 and power emit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 42 publications
2
49
0
5
Order By: Relevance
“…These garments were used for 10 hours as sleepwear over three successive nights to relieve delayed-onset muscle soreness at 48 h after an intense plyometric exercise session [33]. …”
Section: New Development and Application Of Infrared Therapy In Bimentioning
confidence: 99%
“…These garments were used for 10 hours as sleepwear over three successive nights to relieve delayed-onset muscle soreness at 48 h after an intense plyometric exercise session [33]. …”
Section: New Development and Application Of Infrared Therapy In Bimentioning
confidence: 99%
“…Strategies that aid skeletal muscle recovery from damage and promote anti-inflammatory responses via practical methods are deemed critical. Hence, recently use of bioceramic materials, also called Far-Infrared Emitting Ceramic Materials (cFIR), has been proposed as a post-exercise recovery method (Hausswirth et al, 2011;Loturco et al, 2016). Previous in vitro and animal model studies report that the emitted heat and radiation from FIR materials can increase blood circulation, facilitate cell growth (Vatansever and Hamblin, 2012) and tissue regeneration (Segovia et al, 2003), leading to calcium-dependent nitric oxide (NO) and calmodulin upregulation in different cell lines (Leung et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramics are produced by a combination of oxides (Vatansever and Hamblin, 2012), which reflect/emit high-performance farinfrared rays (FIR) (Segovia et al, 2003). FIRemitting polymers or ceramic nanoparticles have recently been incorporated into sports apparel to aid the facilitation and practical application of their use (Cian et al, 2015;Loturco et al, 2016). Accordingly, cFIR have become a promising method to reduce pain and induce tissue repair (Ko and Berbrayer, 2002;Leung et al, 2012;Loturco et al, 2016;Vatansever and Hamblin, 2012), however, conflicting results were reported regarding postexercise recovery improvement (Hausswirth et al, 2011;Leung et al, 2013;Loturco et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Noponen [1] also found an increase in the recovery of anaerobic performance in power athletes when compared to the passive recovery modality. Laturco [14] revealed that FIR administration reduced Delayed Onset Muscle Soreness (DOMS) felt after plyometric training. Some studies state that heat therapy accelerates recovery more than cold therapy or passive recovery by sitting still.…”
Section: Resultsmentioning
confidence: 99%